Thrombosis-Related Loss of Arterial Lines in the First Wave of COVID-19 and Non–COVID-19 Intensive Care Unit Patients. (11th October 2022) - Zon, Rebecca L.; Merz, Lauren E.; Fields, Kara G.; Grandoni, Jessica; Stuart, Jessica C.; Occhiogrosso, Rachel H.; Li, Linda; Baron, Rebecca M.; Fredenburgh, Laura E.; Woolley, Ann E.; Connors, Jean M.; Frendl, Gyorgy
Abstract : BACKGROUND: Patients with coronavirus disease 2019 (COVID-19) can present with severe respiratory distress requiring intensive care unit (ICU)–level care. Such care often requires placement of an arterial line for monitoring of pulmonary disease progression, hemodynamics, and laboratory tests. During the first wave of the COVID-19 pandemic in March 2020, experienced physicians anecdotally reported multiple attempts, decreased insertion durations, and greater need for replacement of arterial lines in patients with COVID-19 due to persistent thrombosis. Because invasive procedures in patients with COVID-19 may increase the risk for caregiver infection, better defining difficulties in maintaining arterial lines in COVID-19 patients is important. We sought to explore the association between COVID-19 infection and arterial line thrombosis in critically ill patients. METHODS: In this primary exploratory analysis, a multivariable Fine-Gray subdistribution hazard model was used to retrospectively estimate the association between critically ill COVID-19 (versus sepsis/acute respiratory distress syndrome [ARDS]) patients and the risk of arterial line removal for thrombosis (with arterial line removal for any other reason treated as a competing risk). As a sensitivity analysis, we compared the number of arterial line clots per 1000 arterial line days between critically ill COVID-19 and sepsis/ARDS patients using multivariable negative binomial regression. RESULTS: We retrospectively identified 119 patients and 200 arterial line insertions in patients with COVID-19 and 54 patients and 68 arterial line insertions with non-COVID ARDS. Using a Fine-Gray subdistribution hazard model, we found the adjusted subdistribution hazard ratio (95% confidence interval [CI]) for arterial line clot to be 2.18 (1.06–4.46) for arterial lines placed in COVID-19 patients versus non–COVID-19 sepsis/ARDS patients ( P = .034). Patients with COVID-19 had 36.3 arterial line clots per 1000 arterial line days compared to 19.1 arterial line clots per 1000 arterial line days in patients without COVID-19 (adjusted incidence rate ratio [IRR] [95% CI], 1.78 [0.94–3.39]; P = .078). CONCLUSIONS: Our study suggests that arterial line complications due to thrombosis are more likely in COVID-19 patients and supports the need for further research on the association between COVID-19 and arterial line dysfunction requiring replacement.